Hierarchical inverse opal hydrogel coatings for superhydrophobic, antibacterial, and drug-responsive catheter interfaces - Liu, Yuegao; Hou, Yijun; Fei, Kaihong; Fu, Songchao; Cheng, Li; Zhou, Lei; Deng, Huibiao; Hu, Shuqin (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionCatheter-related infections and biofouling remain critical challenges in clinical practice due to limited surface functionalities and rapid bacterial biofilm formation.MethodsWe developed a universal bottom-up strategy to fabricate hierarchical inverse opal hydrogel coatings on medical catheters via dopamine-mediated substrate activation, dual-layer colloidal assembly, and polymer infiltration, followed by oil infusion to enable adaptive wettability and low-friction liquid mobility.ResultsThe coatings exhibited stress-responsive wetting transitions, structural-color-enabled visual monitoring of degradation, and tunable droplet adhesion by modulating pore geometry. In vitro tests showed 98.9% antibacterial efficiency against E. coli, together with excellent hemocompatibility, cytocompatibility, and in vivo biosafety.DiscussionBy integrating passive antifouling, controlled drug release, and real-time structural feedback in a single interface, this platform provides a robust route toward infection-resistant and intelligent catheter devices.